Factor associated with quality of life among main caregivers with child of autism in selected non profitable NGO Autism Centre in Klang Valley / Siti Fairus Asahar - Asahar, Siti Fairus (2019)
Introduction and aim: Autism is a lifelong neurodevelopmental condition with challenging needs in relation to neurodevelopment, communication, social and behavioural domains. Having a child with autism spectrum disorders has shown to significantly reduce the quality of life of the caregiver, but locally, there are limited data available on sociademographic factors associated quality of life of main caregiver with child of autism. Methods: A cross sectional study was conducted between June and October 2018. Using stratified convenient sampling, six non-profitable centres were selected. Main caregivers were identified via a defined criterion who fulfilled the inclusion criteria, which include having at least one child with autism between the age of 3 to 9 years old, having the diagnosis of autism confirmed by health care professional and are able to understand English language. Sociodemographic factors of main caregiver and child with autism were obtained. Quality of life of main caregiver was assessed using the Quality of Life in Autism Questionnaire (QoLA), with 28-items QoLA Part A assessing parents’ overall perception of their quality of life and 20-item QOLA Part B assessing the parents’ perception on the impact of child autism symptoms towards them were. The results: A total of 116 main caregivers were included in the final analysis. There were more mother as the main caregivers at 93 (80.2%). The mean quality of life score among main caregiver was 88.55 ± 17.25 and mean perception of the impact of child autism symptoms towards them was 56.55 ± 12.35. Five factors possitively correlated with QoL which were postgraduate qualification, attending parent training session more than two-times a year, attending paediatric clinic, having child’s grandparent and maid to help with the child and having a child who talk in words or sentences for communicating needs. Two factors negatively correlated with QoL were staying in an apartment and main caregiver with anxiety comorbid. Conclusions: Having child with autism affect the quality of life of the main caregivers. Intervention or support towards the main cargivers by considering the factors that affect he QoL positively or negatively is needed to potentially increase the QoL of caregivers.